Skrifter udgivet af Grundtvig-selskabet - Lundgreen-Nielsen, Flemming; Michelsen, William; Pedersen, Kim Arne; Schjørring, Jens Holger (Grundtvig-Studier, 2000)
Works published by the Grundtvig Society